Astronomia no ensino médio, a ciência e o lúdico: desafiando e educando - Carrilho, João José da Silva (2015)
This master thesis presents the results of the use of a didactic material called Experimental Activity Kit (KAE), which was intended to draw up an Experimental Activities Manual (MAE) for teaching astronomy, physics and mathematics. This material was influenced by the teachings of David Ausubel about meaningful learning and Lev Vygotsky, with the theory of acquiring knowledge through practical activity in a social environment. The study was developed during high school physics classes in Feira de Santana, Bahia, between 2014 and 2015, in which the students had to assembly the kits and observe physics and astronomical phenomena. In order to measure the knowledge acquired by the participants in this training process, we perform pre and post-tests with questions that allowed extract important results and conclusions. The results of the exams and evaluation of the methodology, submitted to a content analysis, indicated that students who saw reasoning as emerging through the assembly of the kits developed higher cognitive functions and showed greater interest and excitement in class, confirming that experimentation is one of the factors that most pleased the students during the lessons. This indicates the necessity of a new approach and use hands-on activities, even knowing that many strategies are already available, we believe that the use of MAE brings important contributions, which are described along this work.